Perspektif Prospek: Potensi dan Kendala Sektor Pertanian pada Zona Sub DAS Rawas di Kabupaten Musi Rawas Utara Sumatera Selatan - Chuzaimah Chuzaimah; F. Sjarkowi; E. Wildayana; Yunita Yunita (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2018)
Chuzaimah et al, 2018. Prospect Perspective: Potential and Constraints of the Agricultural Sector in Rawas Sub-watershed Zone in Musi Rawas district, South Sumatra. JLSO 7(2):174-184.Land resources play a very important role in all sectors of economic development. Musi Rawas Utara District is one of 17 districts or cities in the administrative area of South Sumatra Province, which is the youngest district in the Province.This research aimed to analysis of 1) potential and 2) constraints of the agricultural sector in Rawas Sub-watershed Zone in Musi Rawas District, South Sumatra.This research was carried out in Musi Rawas Utara District. Primary data was based on questioner. Whereas secondary data was obtained from relevant agencies or institutions as well as literatures related to this paper. The results showed that there were several potentials and constraints of the agricultural sector in North Musi Rawas District. The potential that exists in terms of land use is remaining a large area of suitable land for agriculture. Land in Musi Rawas Utara District in 2014 was mostly used as a mixed plantation, which was 3,516.47 km² or reached 57.99% of the total the district area and spread throughout the sub-districts. The second widest use was 1,731.42 km² or 28.82% of the land in this District is still in the form of forests, both protected forests (1,604.07 km²) and secondary dry land forests (127.35 km²). The existing constraints in North Musi Rawas District are floods, forest fires, landslides and drought.